Prognostic role of inflammatory and tumor biomarkers in hilar cholangiocarcinoma patients receiving postoperative adjuvant therapy - Zeng, Di; Saad, Saud Ahmad; You, Zhen; Cheng, Nansheng (Frontiers in Oncology, 2025)
BackgroundHilar cholangiocarcinoma (HCCA) is an aggressive cancer with poor prognosis after surgery. The systemic immune-inflammation index (SII) has been proposed as a prognostic marker, but its relationship with other markers such as CA19-9 remains unclear. This study investigates the prognostic significance of SII and CA19-9 in HCCA patients receiving post-surgery adjuvant therapy.MethodsA cohort of 145 HCCA patients who underwent surgery and adjuvant therapy was analyzed. Patients were categorized into High SII and Low SII groups based on an optimal cutoff value of 672.8, determined using ROC curve analysis. Further stratification was performed based on CA19-9 levels. The associations between SII, CA19-9, and survival outcomes, including overall survival (OS) and disease-free survival (DFS), were assessed using Kaplan-Meier survival analysis and Cox proportional hazards regression.ResultsElevated SII was significantly associated with worse OS (p = 0.0027) and DFS (p = 0.0024). Notably, a significant difference in CA19-9 levels was observed between high and low SII groups (p = 0.013), with higher CA19-9 levels in the high SII group. However, no significant difference in CA19-9 was found between the low SII groups (p = 0.128). Patients with both high SII and high CA19-9 levels had the poorest survival outcomes, with significantly higher risks of mortality and disease recurrence (HR for OS = 2.29, 95% CI: 1.23–4.25; HR for DFS = 2.16, 95% CI: 1.17–3.99). Multivariate analysis identified high SII, high CA19-9, lymph node metastasis, and local organ metastasis as independent prognostic factors.ConclusionsElevated SII and CA19-9 are independent prognostic markers for HCCA patients after surgery. The combination of high SII and high CA19-9 identifies a subgroup with the poorest prognosis, suggesting the potential for these markers to guide postoperative treatment decisions.